The time sensitivity of aspirational interventions: Evidence from a role-modeling RCT - Prateek Chandra Bhan; Max Schroeder; Damiano Turchet; Jinglin Wen (PLoS ONE, 2026)
This paper investigates the short-run effects of an aspiration-raising intervention delivered as part of a randomized controlled trial among postgraduate students at a UK university during the Covid-19 pandemic. We document suggestive evidence, that a video-based role-modeling intervention led to an immediate increase in aspirations and a delayed increase in self-reported effort. However, both effects dissipated within a few weeks. Our findings suggest that timing and reinforcement are important considerations for the sustained effectiveness of aspiration-building strategies.